Aktivitas masyarakat jawa dalam novel Bumi Manusia karya Pramoedya Ananta Toer: Kajian antropologi sastra - Bebryana Ratri; Sarwiji Suwandi; Andayani Andayani (Universitas Ahmad Dahlan, 2020)
This research aims to describe the complexity cultures consisting of kinship activities, economy, education, beauty and recreation, religion, politics, and physical needs in the novel Bumi Manusia written by Pramoedya Ananta Toer. The approach used in this research is the anthropology literature approach. Read notes, literature, and description of the analysis are methods used in collecting the data. Meanwhile, the data analysis technique used is descriptive qualitative analysis. The results obtained are (1) kinship activities: helping each other, visiting houses and caring among human, (2) economic activities: complementing the needs of human life, (3) educational activities: formal and non formal, (4) beauty and recreation activities: the art of motion and the art of sound done by human, (5) religious activities: marriage and mutual respect for every beliefs between people, (6) political activities: the fields of government and organization, and (7) physical needs activities: the fields of food, beverages, and clothing.